A parabola whose vertex is the point V = ( 2 , 3 ) and whose focus is ( 5 , 6 ) has equation a x 2 + b x y + c y 2 + d x + e y + f = 0 , where g cd ( a , b , c , d , e , f ) = 1 .
Find ∣ ∣ a + b + c + d + e + f ∣ ∣ .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Same as I have done it. But this is really a boring parabola problem.
Same way. Yesterday I posted a similar problem here
When you put point Q in point-slope form, shouldn't have been y + 0 = -1(x + 1) due to it being y - y^1 = m(x - x^1)? If I'm wrong please inform me why so I can have a better understanding.
Log in to reply
Yes, you are right, thanks. Hopefully the final equation of that line is the same.
Distance between focus and vertex is 3 2 , so if the parabola were canonical its equation would have been y 2 = 1 2 2 x . The slope of the line between the vertex and the focus is 1, so in order to obtain this parabola from the canonical one we need to rotate by 45 degrees, then translate. Let [ u v ] = [ 2 3 ] + [ 2 2 2 2 − 2 2 2 2 ] [ x y ] . A simple calculation shows: u + v = 5 + 2 x , u − v = − 1 − 2 y , So that y 2 = 2 ( v − u − 1 ) 2 and x = 2 u + v − 5 . Substitute in the original equation to get v 2 − 2 u v + u 2 − 2 6 v − 2 2 u + 1 2 1 = 0 .
from where u write matrix equation?
Problem Loading...
Note Loading...
Set Loading...
First we find the slope of the equation that passes through V and F , which is called the focal axis:
m = 5 − 2 6 − 3 = 1
Now, we will find the directrix, but to do that we need to find a new point Q , such that V is the midpoint of F Q , so we will apply the formula of a midpoint with Q = ( a , b ) :
2 = 2 5 + a ⟹ a = − 1
3 = 2 6 + b ⟹ b = 0
Hence, Q = ( − 1 , 0 ) . Now, we also need to find the slope of the perpendicular line to the focal axis, that is: m ′ = − m 1 = − 1 1 = − 1 .
With that, now we can find the directrix, knowing its slope ( m ′ ) and a point ( Q ):
y − 0 = − 1 ( x + 1 ) ⟹ x + y + 1 = 0
Finally, we find our parabola (points P = ( x , y ) ) applying its definition:
F P = distance from x + y + 1 = 0 to P
( x − 5 ) 2 + ( y − 6 ) 2 = 2 ∣ x + y + 1 ∣
Square both sides, expand and simplify:
( x − 5 ) 2 + ( y − 6 ) 2 = 2 ( x + y + 1 ) 2
2 ( x 2 − 1 0 x + 2 5 + y 2 − 1 2 y + 3 6 ) = x 2 + y 2 + 1 + 2 x y + 2 x + 2 y
x 2 − 2 x y + y 2 − 2 2 x − 2 6 y + 1 2 1 = 0
Hence, a = 1 , b = − 2 , c = 1 , d = − 2 2 , e = − 2 6 , f = 1 2 1 and ∣ a + b + c + d + e + f ∣ = 7 3 .